The Development of E-Learning Systems Application Based On Cloud Computing For Higher Education - M. Budi Hartanto (Universitas Bandar Lampung (UBL), 2013)
An E-Learning systems used internet technology to provide data base used for the activity of studying for higher education institution. In order to achieve the way of communication through information technology, cloud computing is a new science in the field of informatics that make the activity more fluent and easy to use. Managing students through e-learning will give positive impact to the development of e-learning systems.This paper discusses about the development of E-Learning Systems Application Based On Cloud Computing as an immerge of information technology for higher education. There are some models of E-Learning that can be applied to help students and lectures in the activity of education with terms of collaborating, coordinating and inspecting.The results expected with this paper is that there is more preparation for higher education in providing and building their own systems by installing some important aspects such as security, viability and quick response to make internet as a smart media in achieving the goal of higher eduaction by using internet.